Questions Used by the Teachers in Teaching Reading Comprehension in English Classroom Interaction - Fitri Orlince Siburian; Anni Holila Pulungan (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2022)
This study aimed (1) To investigate the types of questions used in teaching reading comprehension in English classroom interaction, (2) To analyze how the teachers use the questions in teaching reading comprehension in English classroom interaction, (3) To investigate the reasons why the teachers use the questions the way they do. A descriptive qualitative study was used in this study. The source of the data was two English teachers of class XI in SMA Negeri 1 Sumbul. The data were collected by using video recording and unstructured interview with teachers. The data were the sentences that consist of teachers’ questions in teaching reading comprehension and the result of the teachers’ interview. The data were analyzed by data condensation, data display and conclusion drawing/verification. The findings of the result were that: (1) There were five types of questions used by teachers namely literal questions (9.86%), reorganization or reinterpretation questions 19 (26.76%), inference questions 9 (12.68%), evaluation questions 4 (5.63%) and personal response questions 5 (7.04%). It also found that there were 27 (38.03%) other types of questions used by the two teachers, namely questions related to knowledge, vocabulary and students' experience, (2) The teachers use the different way in giving the questions. KP used wait time, repetition, paraphrasing, simplification and probing, while RS only use wait time, repetition, paraphrasing and simplification in giving questions when teaching reading comprehension, (3) The reasons that affect the teachers do the way they do consist of teachers' experience, teachers' formative and teachers' personal attributes.